PEA/Polydatin: Anti-Inflammatory and Antioxidant Approach to Counteract DNBS-Induced Colitis - Alessio Filippo Peritore; Ramona D’Amico; Marika Cordaro; Rosalba Siracusa; Roberta Fusco; Enrico Gugliandolo; Tiziana Genovese; Rosalia Crupi; Rosanna Di Paola; Salvatore Cuzzocrea; Daniela Impellizzeri (Antioxidants, 2021)
Palmitoylethanolamide (PEA) has well-known anti-inflammatory effects. However, PEA does not possess an antioxidant ability. A comicronized formulation of ultramicronized PEA (um-PEA) and polydatin (Pol) PEA/Pol, a biological precursor of resveratrol with antioxidant activity, could have protective effects on oxidative stress produced by inflammatory processes. We evaluated the effects of a comicronized PEA/Pol 10 mg/kg (9 mg of um-PEA+1 mg of polydatin) in a model of Dinitrobenzene sulfonic acid (DNBS)-induced colitis. Ulcerative colitis was induced in mice by intrarectally injection of DNBS (4 mg in 100 µL of 50% ethanol per mouse). Macroscopic and histologic colon alterations and marked clinical signs were observed four days after DNBS and elevated cytokine production. The myeloperoxidase (MPO) activity assessed for neutrophil infiltration was associated with ICAM-1 and P-selectin adhesion controls in colons. Oxidative stress was detected with increased poly ADP-ribose polymerase (PARP) and nitrotyrosine positive staining and malondialdehyde (MDA) levels in inflamed colons. Macroscopic and histologic alterations minimized by oral PEA/Pol, as well as neutrophil infiltration, inflammatory cytokine release, MDA, nitrotyrosine, PARP and ICAM-1, and P-selectin expressions. The mechanism of action of PEA/Pol could be related to the sirtuin 1/nuclear factor erythroid 2-related factor 2 (SIRT-1/Nrf2) pathway and nuclear factor (NF)-κB. PEA/Pol administration inhibited NF-κB and increased SIRT-1/Nrf2 expressions. Our results show that PEA/Pol is capable of decreasing inflammatory bowel disease (IBD) DNBS-induced in mice.